DAMPAK SOSIAL EKONOMI PENGARUH ERUPSI SINABUNG TERHADAP PENDAPATAN, PENDIDIKAN DAN KESEHATAN MASYARAKAT DI KABUPATEN KARO - Juliana Simbolon; Posman HP Marpaung; Roida Sinaga; Gita Lestari (Universitas Quality, 2019)
In this study, there are several things that can describe the socio-economic conditions of farmers having differences in income, education, and health levels, among others: 1. The highest level of income is in Siosar Suka Meriah Village, because they receive government assistance in the form of land, funds , subsidized fertilizers, and seeds, while in Kuta Tengah Village Shelter the income is lower because the government only provides temporary shelter. The lack of capital also caused the lack of income and land to not allow farming because it was located on the slopes of Mount Sinabung. 2. The education level in Siosar Suka Meriah Village is lower, because after moving to relocation the distance to school is too far and some children do not want to continue their education. Whereas in Kuta Tengah Village Shelter their education is higher, because the distance to school is not too far away and most children also have the desire to go to school. 3. The health level in Siosar Suka Meriah Village and the level of health in the Kuta Tengah Village Shelter together use BPJS / KIS which is programmed by the government for the Mount Sinabung eruption refugee community.